Burden of carpal tunnel syndrome and its associated factors among construction industry workers in Gondar town, Ethiopia - Nigus Bicha; Moges Gashaw; Moges Gashaw; Samuel Teferi Chanie; Melisew Mekie; Ermias Solomon Yalew (Frontiers Media S.A., 2024)
BackgroundCarpal tunnel syndrome is characterized by symptoms such as pain, numbness, or tingling on the anterior surface of the index, middle, or radial half of the ring finger, which is frequently associated with weakness of hand grip, and nocturnal pain and/or numbness resulting from compression of the median nerve at the carpal tunnel between the carpal bones and the transverse ligament. The construction industry involves many activities aside from the building process, such as landscaping, painting, electrical supply, plastering, paving, and telecommunications. Performing such tasks involves repetition of wrist flexion and extension, forceful grip with the hand, and/or vibrations of the hand and arm. This study aimed to assess the prevalence of carpal tunnel syndrome and its associated risk factors among construction workers.MethodAn institutional-based cross-sectional study design was conducted among six construction sectors in Gondar from April to July 2021. An interviewer-administered questionnaire was prepared from the literature with a Katz hand diagram, and a physical examination and a special test (carpal compression test, Phalen's, and Tinel's test) were carried out for those participants who reported pain during the interview. Binary logistic regression was conducted with SPSS 25 to identify the associated risk factors for carpal tunnel syndrome. The strength of the association was detected by the adjusted odds ratio.ResultA total of 333 study participants aged 18-70 years were included in this study. Among the participants, 11.7% (AOR: 95%CI: 8.1-15.3) had carpal tunnel syndrome. Age, cigarette smoking, work experience, and working with finger-pressing tools were risk factors significantly associated with carpal tunnel syndrome among construction workers with a p-value of <0.05.ConclusionThe magnitude of carpal tunnel syndrome was 11.7% among construction workers. Being of older age, having more experience, cigarette smoking, and working with finger-pressing tools were risk factors significantly associated with carpal tunnel syndrome among construction workers. Employers should implement work safety education programs that raise awareness about the risks of cigarette smoking and encourage employers and supervisors to seek early medical intervention and treatment for carpal tunnel syndrome before it becomes a chronic problem.